Association of Change in Alcohol Consumption With Risk of Ischemic Stroke. Issue 8 (20th April 2022) - Jeong, Su-Min; Lee, Han Rim; Han, Kyungdo; Jeon, Keun Hye; Kim, Dahye; Yoo, Jung Eun; Cho, Mi Hee; Chun, Sohyun; Lee, Seung Pyo; Nam, Ki-Woong; Shin, Dong Wook
Abstract : Background: The effect of serial change in alcohol consumption on stroke risk has been limitedly evaluated. We investigated the association of change in alcohol consumption with risk of stroke. Methods: This study is a population-based retrospective cohort study from National Health Insurance Service database of all Koreans. Four lakh five hundred thirteen thousand seven hundred forty-six participants aged ≥40 years who underwent 2 subsequent national health examinations in both 2009 and 2011. Alcohol consumption was assessed by average alcohol intake (g/day) based on self-questionnaires and categorized into non-, mild, moderate, and heavy drinking. Change in alcohol consumption was defined by shift of category from baseline. Cox proportional hazards model was used with adjustment for age, sex, smoking status, regular exercise, socioeconomic information, and comorbidities, Charlson Comorbidity Index, systolic blood pressure, and laboratory results. Subgroup analysis among those with the third examination was conducted to reflect further change in alcohol consumption. Results: During 28 424 497 person-years of follow-up, 74 923 ischemic stroke events were identified. Sustained mild drinking was associated with a decreased risk of ischemic stroke (adjusted hazard ratio, 0.88 [95% CI, 0.86–0.90]) compared with sustained nondrinking, whereas sustained heavy drinking was associated with an increased risk of ischemic stroke (adjusted hazard ratio, 1.06 [95% CI, 1.02–1.10]). Increasing alcohol consumption was associated with an increased risk of ischemic stroke (adjusted hazard ratio, 1.11 [95% CI, 1.06–1.17] from mild to moderate; adjusted hazard ratio, 1.28 [95% CI, 1.19–1.38] from mild to heavy) compared with sustained mild drinkers. Reduction of alcohol consumption from heavy to mild level was associated with 17% decreased risk of ischemic stroke through 3× of examinations. Conclusions: Light-to-moderate alcohol consumption is associated with a decreased risk of ischemic stroke, although it might be not causal and could be impacted by sick people abstaining from drinking. Reduction of alcohol consumption from heavy drinking is associated with a decreased risk of ischemic stroke.